2002
DOI: 10.2118/02-01-02
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the In Situ Recovery of Heavy Oils and Bitumen

Abstract: Most of Canada's trillion barrels of petroleum consists of bitumen, and to a lesser extent, heavy oil. This total may be compared with the total Canadian production of light-medium crude oil to date, which is only 12 billion barrels. Mining is effective for the production of bitumen, but is limited to the minor fraction of the resource that is shallow; also mining involves significant environmental difficulties. The challenges of efficient in situ production are like those for other petroleum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 0 publications
0
21
0
3
Order By: Relevance
“…These then collect below the steam inlet level where they are extracted via a second horizontal production well a few meters below the injection well. Early work indicated that recovery rates of 79-159 m 3 /day can be achieved, with bitumen recoveries of the order of 50% [1,55,56]. SAGD is deemed suitable for unconsolidated reservoirs with high vertical permeability, and is therefore relevant to oil sand deposits for which it is a more environmentally acceptable alternative than mining.…”
Section: Nature Of Steam-based Thermal Recovery Especially Sagd and mentioning
confidence: 99%
See 1 more Smart Citation
“…These then collect below the steam inlet level where they are extracted via a second horizontal production well a few meters below the injection well. Early work indicated that recovery rates of 79-159 m 3 /day can be achieved, with bitumen recoveries of the order of 50% [1,55,56]. SAGD is deemed suitable for unconsolidated reservoirs with high vertical permeability, and is therefore relevant to oil sand deposits for which it is a more environmentally acceptable alternative than mining.…”
Section: Nature Of Steam-based Thermal Recovery Especially Sagd and mentioning
confidence: 99%
“…The various interactions between steam (and any additional components), oil and the reservoir mineralogy determine the efficiency and extent of steam chamber growth, oil displacement, and ultimately potential recovery rates (some aspects of which are broadly expressed by Equation (1)). In the absence of additional steam components, significant residual oil is left behind in the steam chamber (up to 50% recoveries have been quoted, e.g., [1,55,56]), and water is incorporated into the recovered oil.…”
Section: Oil Mobilization Mechanisms In Sagd Processesmentioning
confidence: 99%
“…The upper well in the pair no longer circulates steam but injects it into the reservoir (Irani and Ghannadi 2013). The bitumen flows at the edge of the steam chamber to the production well (Butler et al 1981;Butler and Stephens 1981a, b;Butler and Yee 2002;Chow and Butler 1996).…”
Section: Overview Of Steam-assisted Gravity Drainagementioning
confidence: 99%
“…In the SAGD process, oil flows at the edge of a steam chamber of changing volume in which steam condenses (Butler 1985;Butler 1987;Butler and Kanakia 1994;Butler and Stephens 1981;Butler and Yee 2002;Chow and Butler 1996). Butler By all accounts, the presumption of homogeneity does not hold for Albertan bitumen formations.…”
Section: The Effects Of Non-conformance On Sagd Economicsmentioning
confidence: 99%
“…Credit for this massive shift is due largely to the Steam Assisted Gravity Drainage (SAGD) process as this particular thermal recovery method has increased the country's proven reserves from roughly 7 billion barrels to 175 billion barrels in-situ (Banerjee et al 2013b;Butler and Yee 2002). However, the SAGD process has been open to criticism; the steaming process is seen as wasteful of water and contributes to global greenhouse gas emissions while the economics of the process can be quickly undermined by the inability to produce enough steam from surface facilities or the on-going costs of steam generation (Kovscek 2012).…”
Section: Problem Statementmentioning
confidence: 99%